PENGGUNAAN MODEL PEMBELAJARAN INQUIRY PADA MATA PELAJARAN SEJARAH MATERI IMPERIALISME DAN KOLONIALISME DI SMAN 2 PULAU PUNJUNG KABUPATEN DHARMASRAYA - Valensia Julita; Felia Siska; Juliandry Kurniawan Junaidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the design of the inquiry model in history subjects on the material of imperialism and colonialism at SMAN 2 Pulau Punjung, Dhamasraya Regency. As well as knowing the application in learning using the inquiry model of students in class XI F 1 of SMA Negeri 2 Pulau Punjung on the material of imperialism and colonialism. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research subjects consisted of history teachers and 22 students of class XI F 1. The focus of the research is on how this inquiry model can encourage the way students think critically both in groups and individually. The results of this study that the application of the inquiry model can improve students' ability to think critically, this approach emphasizes the process of searching and discovering knowledge by students actively through questions, exploration, and investigation, this approach also increases curiosity and improves students' communication and collaboration skills. From the results of the interview describes the classroom atmosphere becoming more dynamic, students' understanding of the material increases, and they are better able to relate historical events to the context of current life. The application of the inquiry model also requires researchers to act as facilitators, not simply as transmitters of material, so that the learning process becomes more meaningful and contextual.